Development of Pr2-xSrxCuO4±δ mixed ion-electron conducting system as cathode for intermediate temperature solid oxide fuel cell. (7th June 2019) - Khandale, A.P.; Pahune, B.S.; Bhoga, S.S.; Kumar, R.V.; Tomov, R.
Abstract: Mixed ionic-electronic conducting oxides Pr2- x Sr x CuO4± δ ( x  = 0, 0.2, 0.4, 0.5 and 0.6) are synthesized by combusting mixed precursors (metal acetates) under microwave heating followed by microwave sintering at 1000 °C for 4 h. Each composition of Pr2- x Sr x CuO4± δ solid solutions crystalizes into tetragonal structure within one single phase across the compositional range 0 ≤  x  ≤ 0.5. The T ′-phase Pr2 CuO4± δ transforms to the T *-phase at x  = 0.4. Crystallite size reduces from 801(9) to 728(6) nm with an increase in the Sr content. The maximum dc-conductivity ( σ dc  = 63.1(2) S cm −1 at 700 °C) and minimum activation energy ( E a  = 0.118(3) eV, below pseudo-transition temperature 620 °C) in Pr1.6 Sr0.4 CuO4± δ is ascribed to optimum concentration of extrinsic dissociated defects. The performance of electrochemical symmetrical cells (Pr2- x Sr x CuO4± δ / Ce0.9 Gd0.1 O1.95 / Pr2- x Sr x CuO4± δ ) prepared using inkjet printing is found to be superior than spin coated (cathode) symmetrical cells. Increase in oxygen ion conductivity and surface oxygen exchange reaction rate with increasing Sr dopant concentration improve overall electrochemical performance of cathode. Minimum electrode polarization resistances 0.30(7) Ω cm 2 and 0.21(3) Ω cm 2 (at 700 °C) are obtained for symmetrical cells of Pr1.6 Sr0.4 CuO4± δ cathode using spin-coating and inkjet printing methods, respectively. Electrochemical impedance spectroscopy studies suggest that the charge transfer step is the rate-limiting step during oxygen reduction reaction. Highlights: Pr2- x Sr x CuO4± δ prepared by combustion followed by microwave sintering. Structural phase transition from T' to T* at x  = 0.4. Inkjet printing is superior over spin coating technique. Ion-conductivity and oxygen exchange rate determined from CIS data. Minimum R p (0.3 Ω cm 2 at 700 °C) at x  = 0.4 attributed to extrinsic defects.